1973
DOI: 10.1002/pol.1973.180110603
|View full text |Cite
|
Sign up to set email alerts
|

Approach to generalization of concentration dependence of zero‐shear viscosity in polymer solutions

Abstract: The possibility of constructing zero‐shear viscosity master curves valid for the entire range of concentration for a large number of polymer solutions in different solvents independent of molecular weight and the nature of the solvent is considered. The results obtained show that the parameters characterizing the individual macromolecular chain., viz., the dimensions of the polymer coil and the rheological effectiveness of segmental interactions, are significant in determining the viscosity of polymer solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 26 publications
(4 reference statements)
1
33
0
Order By: Relevance
“…A few such correlations are available in the open literature. Dreval et al (1973) showed that experimental data on polymer solutions for different polymer-solvent combinations can be satisfactorily described by the Martin equation (Davis and Elliott, 1955) over a wide range of conditions. This equation involved a parameter, K M , which, it was suggested, should be taken as a curve-fit parameter so that the correlation could describe data up to reasonably high polymer concentrations.…”
Section: Introductionmentioning
confidence: 93%
“…A few such correlations are available in the open literature. Dreval et al (1973) showed that experimental data on polymer solutions for different polymer-solvent combinations can be satisfactorily described by the Martin equation (Davis and Elliott, 1955) over a wide range of conditions. This equation involved a parameter, K M , which, it was suggested, should be taken as a curve-fit parameter so that the correlation could describe data up to reasonably high polymer concentrations.…”
Section: Introductionmentioning
confidence: 93%
“…When plotting the specific viscosity (Z sp ) as a function of the overlap parameter (C[Z]), [39] a unique curve is obtained for the various dextran samples ( Figure 2). For polymers in good solvent, it has been shown that this curve is well fitted by a polynomial equation [40][41][42][43][44] In Equation (7),…”
Section: Unmodified Dextransmentioning
confidence: 99%
“…(1.106) may be used to identify the concentration at which entanglement constraints become dominant in determining chain mobility. Thus, as shown in Figure 1.12, using data of Dreval et al [1973] on hydroxypropylcellulose solutions in water, Phillies and Quinlan [1995] find a crossover from stretched-exponential to power-law concentration dependence, η ∼ c ε , signifying what they term a solutionlike-meltlike transition in polymer dynamics. As shown in Figure 1.12, the crossover occurs at the concentration c[η] ∼ 20 (i.e., considerably in excess of the overlap concentration, c * [η] ∼ 1.0).…”
Section: Predictive Models For Solutions Of Flexible Neutral Polymersmentioning
confidence: 99%